ATP-Binding Cassette Transporter VcaM from Vibrio cholerae is Dependent on the Outer Membrane Factor Family for Its Function - Wen-Jung Lu (International Journal of Molecular Sciences, 2018)
Vibrio cholerae ATP-binding cassette transporter VcaM (V. cholerae ABC multidrug resistance pump) has previously been shown to confer resistance to a variety of medically important drugs. In this study, we set to analyse its properties both in vitro in detergent-solubilised state and in vivo to differentiate its dependency on auxiliary proteins for its function. We report the first detailed kinetic parameters of purified VcaM and the rate of phosphate (Pi) production. To determine the possible functional dependencies of VcaM on the tripartite efflux pumps we then utilized different E. coli strains lacking the principal secondary transporter AcrB (Acriflavine resistance protein), as well as cells lacking the outer membrane factor (OMF) TolC (Tolerance to colicins). Consistent with the ATPase function of VcaM we found it to be susceptible to sodium orthovanadate (NaOV), however, we also found a clear dependency of VcaM function on TolC. Inhibitors targeting secondary active transporters had no effects on either VcaM-conferred resistance or Hoechst 33342 accumulation, suggesting that VcaM might be capable of engaging with the TolC-channel without periplasmic mediation by additional transporters. Our findings are indicative of VcaM being capable of a one-step substrate translocation from cytosol to extracellular space utilising the TolC-channel, making it the only multidrug ABC-transporter outside of the MacB-family with demonstrable TolC-dependency.